Justice for Women : concerns and expressions - Anand, Adarsh Sein, 1936-; Gandhi, Munisha (New Delhi : Universal Law Pub. Co., 2008)
Chiefly comprises courts judgments; includes articles on issues related to women
Keywords: Women -- Legal status, laws, etc. -- India